Characterization and evaluation of the morphological attributes of Ethiopian mustard (Brassica carinata A. Braun) landraces - Rahiel Hagos Abraha; Abdulwahab S. Shaibu; Jianli Liang; Jian Wu; Runmao Lin; Xiaowu Wang (Euphytica, 2024)
Ethiopian mustard ( Brassica carinata A. Braun) is one of the Brassica leafy vegetables and oilseed crops, which can withstand adverse environmental conditions. This study was conducted to characterize and evaluate the leaf attributes of 313 Ethiopian mustard accessions grown in the greenhouse and field in 2018/19 in Beijing, China. Data on 18 different leaf morphological attributes were collected based on the IBPGR for Brassica and Raphanus descriptor format and Fiji Image J. The collected data were subjected to descriptive statistics using JMP version 14 software. Results indicate that the majority of the accessions had serrated leaf margin, intermediate juvenile development, rounded apex leaf shape, absence of leaf pubescence, number of lobes > 5 and had intermediate number of leaves per plant with frequencies of 101, 213, 223, 244, 183 and 289, respectively. The accessions had also white midrib color, light green leaf color, purple petiole color, purple stem color and purple apex leaf color pigments with frequencies of 168, 165, 104, 113 and 122, respectively. Significant differences were observed among the accessions for leaf size attributes ( p < 0.001) indicating their potential as leafy vegetables. Furthermore, there were significant accession × environment effects for the laminal length, total leaf length, leaf area, leaf weight and petiole length. Notably, 71% of the accessions had an average of 81 days flowering time. The multivariate cluster and principal component analyses divided the 313 accessions into eight groups with distinctive information; consisting of 81, 37, 79, 38, 14, 11, 6 and 47 accessions. Thus, this study provides important information about Ethiopian mustard germplasms that is vital for further advancement and genetic improvement of the crop.